Is environmental regulation a blessing or a curse for China's urban land use efficiency? Evidence from a threshold effect model. (8th January 2021) - Zhang, Xupeng; Lu, Xinhai; Chen, Danling; Zhang, Chaozheng; Ge, Kun; Kuang, Bing; Liu, Sui
Abstract: Severe land shortage causes a higher demand for domestic and foreign land‐intensive products. As a result, resource utilization, and related environmental issues, will increase in urban areas. To this respect, the analysis of the impact of environmental regulation on urban land use efficiency helps to identify potential points for interventions designed to ensure sustainable land use. This study first introduces a theoretical framework to investigate the micro‐transmission mechanism of environmental regulation on urban land use efficiency. Our profit decision‐making model concludes that the impact of environmental regulation on urban land use efficiency is influenced by changes in the industrial structure. Empirically, our preliminary analysis suggests that in addition to population density, both formal and informal environmental regulation can promote urban land use efficiency, with a significant spatial heterogeneity across the sample regions. Further, this study shows a remarkable double‐threshold relationship between formal environmental regulation and urban land use efficiency in China. We clarify and confirm that environmental regulation promoted urban land use efficiency only when regulation intensity was higher than 0.8612. Environmental regulation increased urban land use efficiency in high‐level industrial rationalization areas, whereas it had the opposite effect in low‐level ones. Furthermore, there was a clear marginal diminishing effect of the impact of environmental regulation on urban land use efficiency when the optimization of the industrial structure was set as a threshold variable.